Strategi Pengembangan Ekonomi Kreatif di Era Digital: Studi Kasus Zydnaa Edukasi Jombang - Imma Rokhmatul Aysa (Jurnal At-Tamwil: Kajian Ekonomi Syariah, 2020)
Zydnaa education as a creative economy actor is creating a creative work whose results can be useful for the community, especially in the world of education. This study aims to analyze the strategies that have been carried out by Zydnaa Education in developing its products in the current digital era so that they can survive even in the midst of the Covid-19 outbreak that hit Indonesia. Research on creative economic development strategies is carried out using a qualitative approach with a case study technique. The data used in this research consists of primary data (owner) and secondary data (literature). The technique of determining informants using purposive sampling. From the research results, it was found that the strategies implemented by zydnaa education consist of internal factors (strengths and opportunities) and external (weaknesses and threats). Whereas suggestions from researchers for educational zydnaa related to strategies that will be taken in the future include collaborating with formal or non-formal educational institutions to distribute their products as learning tools that are of interest to children, making simple financial reports regularly both monthly and annually, and adding a positive image of the business because it will appear to be implementing professional business practices.